The Influence of Countermovement Jump Protocol on Reactive Strength Index Modified and Flight Time: Contraction Time in Collegiate Basketball Players - Aaron Heishman; Brady Brown; Bryce Daub; Ryan Miller; Eduardo Freitas; Michael Bemben (MDPI AG, 2019)
The purpose of the present investigation was to evaluate differences in Reactive Strength Index Modified (RSIMod) and Flight Time to Contraction Time Ratio (FT:CT) during the countermovement jump (CMJ) performed without the arm swing (CMJNAS) compared to the CMJ with the arm swing (CMJAS), while exploring the relationship within each variable between jump protocols. A secondary purpose sought to explore the relationship between RSIMod and FT:CT during both jump protocols. Twenty-two collegiate basketball players performed both three CMJNAS and three CMJAS on a force plate, during two separate testing sessions. RSIMod was calculated by the flight-time (RSIModFT) and impulse-momentum methods (RSIModIMP). CMJ variables were significantly greater during the CMJAS compared to CMJNAS (p < 0.001). There were large to very large correlations within each variable between the CMJAS and CMJNAS. There were significant positive correlations among RSIModFT, RSIModIMP, and FT:CT during both the CMJAS (r ≥ 0.864, p < 0.001) and CMJNAS (r ≥ 0.960, p < 0.001). These findings identify an increase in RSIMod or FT:CT during the CMJAS, that may provide independent information from the CMJNAS. In addition, either RSIMod or FT:CT may be utilized to monitor changes in performance, but simultaneous inclusion may be unnecessary.